2018
DOI: 10.3389/fmicb.2018.00084
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization Reduces Transfer of Diverse Environmental Microbiota Indoors

Abstract: Expanding urbanization is a major factor behind rapidly declining biodiversity. It has been proposed that in urbanized societies, the rarity of contact with diverse environmental microbiota negatively impacts immune function and ultimately increases the risk for allergies and other immune-mediated disorders. Surprisingly, the basic assumption that urbanization reduces exposure to environmental microbiota and its transfer indoors has rarely been examined. We investigated if the land use type around Finnish home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 78 publications
5
106
0
Order By: Relevance
“…Soils including composted gardening materials host especially diverse microbial communities (Yu et al, 2015) and thus increasing contact with such soils for urban citizens could provide a means for increasing the diversity of their microbiota and further decrease the prevalence of asthma and atopies (von Hertzen & Haahtela, 2006). This is especially significant in the light of our earlier findings, which suggest that urbanization and pollution could lead to changes in soil microbiota and urbanization reduces microbial transfer indoors (Parajuli et al, 2017(Parajuli et al, , 2018.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Soils including composted gardening materials host especially diverse microbial communities (Yu et al, 2015) and thus increasing contact with such soils for urban citizens could provide a means for increasing the diversity of their microbiota and further decrease the prevalence of asthma and atopies (von Hertzen & Haahtela, 2006). This is especially significant in the light of our earlier findings, which suggest that urbanization and pollution could lead to changes in soil microbiota and urbanization reduces microbial transfer indoors (Parajuli et al, 2017(Parajuli et al, , 2018.…”
mentioning
confidence: 66%
“…These changes may affect the normal development of immune system in early childhood (Stiemsma, Reynolds, Turvey, & Finlay, ). Most recently, the hygiene hypothesis has been extended to a biodiversity hypothesis (von Hertzen, Hanski, & Haahtela, ), which suggests that the rapid global biodiversity decline is related to the increase in immune‐mediated diseases: the decreased microbial diversity in the urban living environment contributes to the reduction in natural exposure to microorganisms (Parajuli et al., ) and prevent the natural development of immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Are the pets running in and out, are the shoes taken off when stepping in? Parajuli et al studied debris deposited on standardized doormats and confirmed that urban built environment reduces transfer of diverse environmental microbiota indoors.…”
Section: Emerging Biodiversity Hypothesismentioning
confidence: 96%
“…Liddicoat et al (2019) found that disturbed land may favour opportunistic bacteria (including pathogenic strains), albeit in a non‐urban setting, and Talamantes, Behseta, and Zender (2007) found anthropogenically disturbed land can release pathogenic fungal spores. Moreover, densely urbanized environments can prevent the transfer of diverse microbiota indoors (Parajuli et al, 2018), and indoor environments can harbour higher proportions of human associated pathogens (Kembel et al, 2012). As such, creating socially inclusive, high‐quality biodiverse greenspaces may also help to reduce contact with pathogens.…”
Section: Theme 1: Human and Environmental Relationshipsmentioning
confidence: 99%